The nicotinic acetylcholine receptor gene family of the honey bee, Apis mellifera - Jones, Andrew K.; Raymond-Delpech, Valerie; Thany, Steeve H.; Gauthier, Monique; Sattelle, David B. (Genome Research, 2006)
Nicotinic acetylcholine receptors (nAChRs) mediate fast cholinergic synaptic transmission and play roles in many cognitive processes. They are under intense research as potential targets of drugs used to treat neurodegenerative diseases and neurological disorders such as Alzheimer's disease and schizophrenia. Invertebrate nAChRs are targets of anthelmintics as well as a major group of insecticides, the neonicotinoids. The honey bee, Apis mellifera, is one of the most beneficial insects worldwide, playing an important role in crop pollination, and is also a valuable model system for studies on social interaction, sensory processing, learning, and memory. We have used the A. mellifera genome information to characterize the complete honey bee nAChR gene family. Comparison with the fruit fly Drosophila melanogaster and the malaria mosquito Anopheles gambiae shows that the honey bee possesses the largest family of insect nAChR subunits to date (11 members). As with Drosophila and Anopheles, alternative splicing of conserved exons increases receptor diversity. Also, we show that in one honey bee nAChR subunit, six adenosine residues are targeted for RNA A-to-I editing, two of which are evolutionarily conserved in Drosophila melanogaster and Heliothis virescens orthologs, and that the extent of editing increases as the honey bee lifecycle progresses, serving to maximize receptor diversity at the adult stage. These findings on Apis mellifera enhance our understanding of nAChR functional genomics and provide a useful basis for the development of improved insecticides that spare a major beneficial insect species.